A concrete constitutive model considering coupled effects of high temperature and high strain rate. (March 2017) - Yu, Xiao; Chen, Li; Fang, Qin; Ruan, Zheng; Hong, Jian; Xiang, Hengbo
Highlights: A constitutive model considering coupled effects of high temperature and high strain rate for concrete is proposed. Triaxial test data of concrete after different temperatures were used to define the yield criterion of the proposed model at high temperatures. Dependent influence of high temperature and high strain rate on mechanical behavior of concrete was discovered. The numerical models adopted the proposed model shown good agreement with the test data. Abstract: Concrete in RC structures is possibly exposed to fire and blast due to occasional accidents or attacks during the service life. To predict the dynamic responses of RC structures under fire and blast precisely, the Drucker–Prager (DP) constitutive model was modified to consider the coupled effects of high temperature and high strain rate for concrete. The piecewise function for the complete stress–strain curve of concrete at the ambient temperature was extended for damage and high temperatures. The yield criterion with the exponent form and the associated flow rule were employed into the model to describe the plastic behaviors of concrete at high temperature. A new coupling function was proposed to determine the coupled effects of high temperature and high strain rate on concrete strength on base of the test data. The proposed model was implemented into the commercial FE software ABAQUS through VUMAT. A fine numerical analysis on the existing SHPB test at high temperature was conducted to validate the proposed model, and a good agreement with the test data was observed.